Empowerment and health promotion of refugee women - Dantas, Jaya; Lumbus, Anita; Gower, Shelley (Faculty of Health Sciences, Curtin University, 2018)
Women face many challenges during the refugee journey and upon resettlement. They demonstrate great resilience and agency as they navigate a new life for themselves and their families. Understanding settlement from the perspective of refugee women is important in implementing policies and programs which can effectively respond to their needs and issues. The Empowerment and Mental Health Promotion of Refugee Women through Photovoice Project (Photovoice Project), funded by Healthway – the Health Promotion Foundation of Western Australia was conducted in partnership with Ishar Multicultural Women’s Health Centre. The study used photovoice, a participatory research tool. Participants were provided with cameras and asked to photograph items and situations that represented their settlement experience. 43 women of refugee background took part in the Photovoice Project and 22 women selected photographs for a travelling exhibition. Over a third of the women who participated were from Iraq, with others from Iran, Afghanistan, Syria, Vietnam, South Sudan, Eritrea, Somalia, Myanmar, Pakistan, Lebanon and El Salvador. Taking photographs and sharing these with the group was described as an empowering experience. Recommendations proposed by women themselves • The need for English language programs tailored to women’s unique circumstances, recognising issues which impact on learning such as family responsibilities, pre-Australian education, trauma/health issues and cultural adjustment. • Support to gain employment through training, mentoring and building networks. • Resourcing for settlement and women’s services. • Receiving assistance from settled migrants to help new refugees. Photovoice proved to be an effective tool for supporting wellbeing and empowerment among women refugees. Language difficulties, gender issues and social isolation continue to be significant issues experienced among women refugees beginning a new life in Australia. Sustained English language tuition, appropriate to the needs and life demands of women refugees is necessary to support their successful settlement.